Pemberian Buku Cerita Bergambar Bertema "Superhero" dapat Meningkatkan Pengetahuan Sayur dan Buah Siswa Sekolah Dasar - Pradini, Indira; Angkasa, Dudung; Jusat, Idrus; Dewanti, Lintang Purwara; Wahyuni, Yulia (Jurnal Gizi, 2021)
The low consumption of vegetables and fruit in school-age children is one of the unresolved nutritional problems in Indonesia. A way to improve vegetable and fruit eating behavior is to increase students' knowledge and attitudes through illustrated story book and heroic tales. The aim of this study is to find out the impact of picture books on students' knowledge and attitude. This is a quasy experimental study with Non equivalent control group with a pre-test and post-test which was followed by 97 fourth gradeelementary school students including 41 students of intervention group and 56 students of control group. The mann-whitney test is used to see whether there are  relationships between  independent variable (given of illustrated story books) and the dependent variable (knowledge and attitude) between the intervention and control groups.The results showed a significant increase in knowledge and attitudes in the group which given illustrated story book. There were also significant differences in knowledge changes between the intervention and control groups. Illustrated story books can significantly increase students' knowledge about vegetables and fruitKeywords : Knowledge; Attitudes; Vegetable; Fruits; Illustrated Story Book